Management of Oxaliplatin-Induced Peripheral Sensory Neuropathy - Cavaletti, Guido (Cancers (Basel), 2020)
Oxaliplatin-induced peripheral neurotoxicity (OIPN) is a severe and potentially permanent side effect of cancer treatment affecting the majority of oxaliplatin-treated patients, mostly with the onset of acute symptoms, but also with the establishment of a chronic sensory loss that is supposed to be due to dorsal root ganglia neuron damage. The pathogenesis of acute as well as chronic OIPN is still not completely known, and this is a limitation in the identification of effective strategies to prevent or limit their occurrence. Despite intense investigation at the preclinical and clinical levels, no treatment can be suggested for the prevention of OIPN, and only limited evidence for the efficacy of duloxetine in the treatment setting has been provided. In this review, ongoing neuroprotection clinical trials in oxaliplatin-treated patients will be analyzed with particular attention paid to the hypothesis leading to the study, to the trial strengths and weaknesses, and to the outcome measures proposed to test the efficacy of the therapeutic approach. It can be concluded that (1) prevention and treatment of OIPN still remains an important and unmet clinical need, (2) further, high-quality research is mandatory in order to achieve reliable and effective results, and (3) dose and schedule modification of OHP-based chemotherapy is currently the most effective approach to limit the severity of OIPN.